Sweetness & lightning. Vol. 7 - Amagakure, Gido (Kodansha Comics, 2017)
Tsumugi is now in kindergarten, and as she grows up, her questions are becoming more complicated. Her curiosity about her mother leads to a quiet search for an old photo album that brings up memories as beautiful as they are poignant--but when a character in her favorite TV show dies, she begins to ask about "heaven" and "hell," and Kohei will have to find a way to answer. But as always, home cooking-- like candied chestnuts, oyakodon, and somen noodles poured down a bamboo flume--is a balm for the wounded souls of father and daughter alike.